Possibilities for using granodiorite of “Lozjanska Reka” (Village of Kruševica, Western Macedonia) as an architectural stone - Stojkov, Sašo; Spasovski, Orce (Geologica Macedonica, 2014)
The granodiorite of the Lozjanska Reka, western Macedonia, has been examined in order to determine the possibility to be used as an architectural stone. The samples were taken from the surface parts, and the results from their physical and mechanical examination have shown that rock mass itself satisfies all requirements form the use as architectural stone according to the state standards of R. Macedonia. Also the quality of the stone is greater in the deeper parts of the terrain where the influences from the outside have a very small effect. This stone does not have highly decorative features but it has a very fine grained structure which has a positive effect for the technical characteristics and for the being a subject for processing. Key words: granodiorite; Lozjanska Reka; architectural stone; mineralogic-petrographic composition;physical-mechanical characteristics